Dampak Pengangguran, Pertumbuhan Ekonomi dan IPM Terhadap Tingkat Kemiskinan di Provinsi Sulawesi Selatan Dalam Kacamata Ekonomi Islam (Periode 2018-2022) - Prasasti, Riska (ITB AAS INDONESIA Surakarta, 2023)
Unemployment, economic growth, and the Human Development Index are indicators of the region's economic strength, including poverty rates in South Sulawesi. The purpose of this study is to investigate the impact of unemployment rate on poverty rate, the impact of economic growth on poverty rate, and the impact of the Human Development Index (HDI) on poverty rate. The study uses panel data for the period 2018-2022 and uses a quantitative approach processed using reviews. The results of this study show that unemployment rate has no significant impact on poverty rate and economic growth has no significant impact on poverty, but Human Development Index (HDI) has significant impact on poverty in South Sulawesi.